The River Ljubljanica and the phenomenon of medieval swords from the 11th to the 15th century in watery contexts - Gaspari, Andrej (Arheološki vestnik, 2017)
The contribution discusses the phenomenon of the unusually high number of medieval swords recovered from the River Ljubljanica in its stretch across the Ljubljansko barje. The majority of the over 56 sword finds is marked by an absence or lack of context data, which call for a more in-depth analysis of the so-called internal markers of individual finds, such as the state of preservation upon discovery, traces of damage or manipulation and presence/absence of scabbard remains. The results of this analysis add to those of the typo-chronological analysis of weapons and even, to a certain degree, help focus the study on the interpretations or hypotheses concerning the circumstances and causes that brought the swords to the bottom of the river. Given the results of the analyses, the author argues that the chronological structure of the swords, with a peak between the 12th and the mid-14th century, coupled with difficulties in categorising such finds from later periods, a relative paucity of the finds of contemporary pole weapons, as well as horse and riding gear that would suggest more intensive movements in the riparian areas, a concentrated occurrence of swords in certain sections of the riverbed and finally limited risks of accidental loss deriving from the natural environment largely exclude the possibility of repeated accidental loss and support the supposition of an important part of the weapons under discussion being immersed as the result of conscious decisions or intent.